2015
DOI: 10.4049/jimmunol.1401470
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory FcγRIIb-Mediated Soluble Antigen Clearance from Plasma by a pH-Dependent Antigen-Binding Antibody and Its Enhancement by Fc Engineering

Abstract: Fc engineering can modulate the Fc–FcγR interaction and thus enhance the potency of Abs that target membrane-bound Ags, but it has not been applied to Abs that target soluble Ags. In this study, we revealed a previously unknown function of inhibitory FcγRII in vivo and, using an Ab that binds to Ag pH dependently, demonstrated that the function can be exploited to target soluble Ag. Because pH-dependent Ab dissociates Ag in acidic endosome, its Ag clearance from circulation reflects the cellular uptake rate of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 34 publications
1
41
0
Order By: Relevance
“…Recent advances in antibody-engineering technology make it possible to develop not only target-specific therapeutics but also antibodies with various functions, such as bispecific target-binding, agonistic activity, conditional target-binding properties, and effector cell redirection826272829. Of these antibody-based therapeutics, TRABs are attracting attention in the field of cancer immunotherapy8.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in antibody-engineering technology make it possible to develop not only target-specific therapeutics but also antibodies with various functions, such as bispecific target-binding, agonistic activity, conditional target-binding properties, and effector cell redirection826272829. Of these antibody-based therapeutics, TRABs are attracting attention in the field of cancer immunotherapy8.…”
Section: Discussionmentioning
confidence: 99%
“…When the Fc variant was engineered further to introduce the E233D/G237D/P238D/H268D/P271G/A330R mutation (mentioned earlier in Section ‘Sweeping antibody with Fc engineering to increase FcγR binding’, as variant v12), it achieved more than 200‐fold increased binding affinity to FcγRIIb, while binding affinity to human FcγRIIa histidine 131 allotype was 0.068‐fold lower, and binding affinity to human FcγRIIa arginine 131 allotype was only twofold higher than that of wildtype human IgG1. A pH‐dependent antibody with this v12 variant accelerated the antigen clearance from circulation compared to wildtype IgG1 in human FcγRIIb transgenic mice . It was reported that platelet activation mediated by FcγRIIa may cause thrombosis ; hence, selective human FcγRIIb binding can be beneficial, both from the point of sweeping efficiency and from that of safety in an antibody with a pH‐dependent antigen‐binding property.…”
Section: Engineering the Antibody To Generate A Sweeping Antibodymentioning
confidence: 99%
“…Recently, we have demonstrated that mouse FcγR but not FcRn contributes to the uptake into the cell of an antibody–antigen complex with wildtype human and mouse IgG1 . When the FcγR binding of a pH‐dependent anti‐IL‐6 receptor antibody was silenced, hsIL‐6R accumulation in plasma was more than that of the antibody with wildtype IgG1.…”
Section: Effect Of a Sweeping Antibody Against A Soluble Antigenmentioning
confidence: 99%
See 1 more Smart Citation
“…This increased the number of cycles of antigen binding and lysosomal degradation, which, coupled with Fc engineering to increase binding to FcRn, significantly improved both PK and PD in cynomolgus monkeys. Additionally, they showed that the Fc gamma receptor FcγRIIb is a major contributor in the cellular uptake of monomeric immune complexes . Subsequently, the authors expanded the sweeping technology to accelerate the clearance of pH‐dependent anti‐IL‐6R by engineering the Fc to selectively enhance human FcγRIIb (instead of FcRn) binding.…”
Section: Improving Pk Through Antibody Designmentioning
confidence: 99%